Chemical screen reveals small molecules suppressing fragile X premutation rCGG repeat-mediated neurodegeneration in Drosophila - Qurashi, Abrar (Oxford University Press, 2012)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is a progressive neurodegenerative disorder recognized in fragile X premutation carriers. Using Drosophila, we previously identified elongated non-coding CGG repeats in FMR1 allele as the pathogenic cause of FXTAS. Here, we use this same FXTAS Drosophila model to conduct a chemical screen that reveals small molecules that can ameliorate the toxic effects of fragile X premutation ribo-CGG (rCGG) repeats, among them several known phospholipase A(2) (PLA(2)) inhibitors. We show that specific inhibition of PLA(2) activity could mitigate the neuronal deficits caused by fragile X premutation rCGG repeats, including lethality and locomotion deficits. Furthermore, through a genetic screen, we identified a PLA(2) Drosophila ortholog that specifically modulates rCGG repeat-mediated neuronal toxicity. Our results demonstrate the utility of Drosophila models for unbiased small molecule screens and point to PLA(2) as a possible therapeutic target to treat FXTAS.